Solve for t s-3t=rt

Math
s-3t=rt
Subtract rt from both sides of the equation.
s-3t-rt=0
Subtract s from both sides of the equation.
-3t-rt=-s
Factor t out of -3t-rt.
Tap for more steps…
Factor t out of -3t.
t⋅-3-rt=-s
Factor t out of -rt.
t⋅-3+t(-r)=-s
Factor t out of t⋅-3+t(-r).
t(-3-r)=-s
t(-3-r)=-s
Divide each term by -3-r and simplify.
Tap for more steps…
Divide each term in t(-3-r)=-s by -3-r.
t(-3-r)-3-r=-s-3-r
Cancel the common factor of -3-r.
Tap for more steps…
Cancel the common factor.
t(-3-r)-3-r=-s-3-r
Divide t by 1.
t=-s-3-r
t=-s-3-r
Simplify -s-3-r.
Tap for more steps…
Move the negative in front of the fraction.
t=-s-3-r
Rewrite -3 as -1(3).
t=-s-1(3)-r
Factor -1 out of -r.
t=-s-1(3)-(r)
Factor -1 out of -1(3)-(r).
t=-s-1(3+r)
Simplify the expression.
Tap for more steps…
Move the negative in front of the fraction.
t=–s3+r
Multiply -1 by -1.
t=1s3+r
Multiply s3+r by 1.
t=s3+r
t=s3+r
t=s3+r
t=s3+r
Solve for t s-3t=rt

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top